2019
DOI: 10.1007/s11356-018-3964-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing nitrogen and phosphorus removal potential of five plant species in floating treatment wetlands receiving simulated nursery runoff

Abstract: The feasibility of using floating treatment wetlands (FTWs) to treat runoff typical of commercial nurseries was investigated using two 8-week trials with replicated mesocosms. Plants were supported by Beemat rafts. Five monoculture treatments of Agrostis alba (red top), Canna × generalis 'Firebird' (canna lily), Carex stricta (tussock sedge), Iris ensata 'Rising Sun' (Japanese water iris), Panicum virgatum (switchgrass), two mixed species treatments, and an unplanted control were assessed. These plant species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 48 publications
1
10
1
Order By: Relevance
“…(2019) reported higher phosphorus removal due to higher initial concentration by five different plant species. 8 White and Cousins (2019) reported higher nutrient (nitrogen and phosphorus) removal at low concentration compared to that at high concentration, 12 in contrast to the findings of . 8 Initial nutrient concentration has been reported to influence plant biomass production, 13 which in turn regulates nutrient removal rate as the plants grow.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…(2019) reported higher phosphorus removal due to higher initial concentration by five different plant species. 8 White and Cousins (2019) reported higher nutrient (nitrogen and phosphorus) removal at low concentration compared to that at high concentration, 12 in contrast to the findings of . 8 Initial nutrient concentration has been reported to influence plant biomass production, 13 which in turn regulates nutrient removal rate as the plants grow.…”
Section: Introductionmentioning
confidence: 91%
“…8 White and Cousins (2019) reported higher nutrient (nitrogen and phosphorus) removal at low concentration compared to that at high concentration, 12 in contrast to the findings of . 8 Initial nutrient concentration has been reported to influence plant biomass production, 13 which in turn regulates nutrient removal rate as the plants grow. To the best of our knowledge, nutrient removal behavior in FTWs at varying initial concentrations has not been reported by studies other than the above-mentioned sources.…”
Section: Introductionmentioning
confidence: 91%
“…It was reported that plant N uptake by Pontederia cordata and Juncus effusus was in excess of 50% with peak accumulation of nutrients during August and September (a majority of nutrients accumulated in the shoot tissues rather than roots) (Chance et al, 2019). Spangler, Sample, Fox, Albano, & White, 2019 suggested that the plant harvest timing and plant species while treating runoff from commercial nurseries using FTWs have impacted the mass of nutrient remediation. The impact of hydraulics of FTWs and their root systems on the performance of stormwater retention ponds were studied and concluded that FTWs are a viable method to minimize the hydraulic inefficiencies and optimized the hydraulic performance of stormwater retention ponds (Khan, Shoaib, Khan, Melville, & Shamseldin, 2019).…”
Section: Wetlands For Stormwater Treatmentmentioning
confidence: 99%
“…Much of this research has been conducted using monoculture plantings of common wetland plants ( Ipomoea aquatica , Oenanthe javanica , Vetiveria zizanoides , Cyperus papyrus , Eichhornia crassipes , etc. ) Some studies have evaluated plant mixtures, but these primarily are in situ scenarios. Only Spangler et al assessed remediation as influenced by plant mixture, while the others did not account for the individual species contributions or compare the mixture to a species monoculture.…”
Section: Introductionmentioning
confidence: 99%